Mañca bivartana - Āhameda, Māṇika,Śarmā, Sañjīva Kumāra (Asama Prakāśana Pariṣada, 2023)
Compilation of articles on historical tapestry of Assamese drama and stage.
Keywords: Assamese drama; History and criticism.; Theater; India; Assam; History.